Papua New Guinea : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This Selected Issues paper and Statistical Appendix surveys the main reasons for Papua New Guinea's disappointing economic performance, highlighting the key impediments to growth in each of the main sectors of the economy. The paper outlines the structural reforms that could help reduce these impediments, so that Papua New Guinea makes progress toward poverty alleviation and the restoration of sustainable development. The paper also describes the evolution of Papua New Guinea's external debt structure, and assesses the sensitivity of debt dynamics to a number of shocks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet